Penggunaan Bahasa Baku dalam Lingkup Universitas Negeri Medan di Tengah Fenomena Kedwibahasaan - Luisa, Adellia; Rangkuty, Amelia Nurul Oktaviani; Zira, Khairana; Harahap, Safinatul Hasanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by the lack of use of standard language among students which is influenced by the bilingual phenomenon that occurs among teenagers, especially students. In analyzing the data, researchers chose Medan State University students as research objects where data was obtained through distributing questionnaires contained in the Google Form link. This research aims to find out (1) how standard language is used among students, (2) what is the frequency of use of standard language within students, (3) what causes students to find it difficult to use standard language, and (4) what language is used more often by students. students in communicating other than standard language. The results of this research were that 8 people used standard language more often, 7 people used regional language more often and 12 people used slang more often. On average, participants chose to use slang more often than standard or regional language. This is because slang is used more often because the respondents are used to it and are often in environments where slang is also used.